THE REPRESENTATION OF NATIONAL AND SPIRITUAL VALUES IN THE CHARACTER PORTRAYAL IN THE NOVEL “STARLIT NIGHTS” - Isomova Ruxshona (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This article examines the role of national and spiritual values in shaping the characters of heroes in Pirimkul Kadyrov’s historical novel “Starry Nights.” Through the system of central characters in the work, the ethical and aesthetic views of the Uzbek people, as well as the culture of family relationships, are analyzed from a scholarly perspective. The novel presents not only a chronicle of historical events, but also an artistic depiction of the Uzbek national character and spiritual values. Each central character in the work embodies a specific national value. The main manifestations of national and spiritual values are considered through the characters of the key figures.